RUMAH MODERASI BERAGAMA DI PTKI MENCETAK KADER MAHASISWA BERKESADARAN DAKWAH BELA NEGARA - Daniel S, Tumpal; Amelia, Siska (STAI Darul Qalam Tangerang, 2025)
Religious moderation creates awareness of national defense. Article 27 Paragraph 3 of the 1945 Constitution mandates that: